2022
DOI: 10.2217/bmm-2021-0749
|View full text |Cite
|
Sign up to set email alerts
|

Novel Biomarkers for Acute Respiratory Distress Syndrome: Genetics, Epigenetics and Transcriptomics

Abstract: Acute respiratory distress syndrome (ARDS) can be induced by multiple clinical factors, including sepsis, acute pancreatitis, trauma, intestinal ischemia/reperfusion and burns. However, these factors alone may poorly explain the risk and outcomes of ARDS. Emerging evidence suggests that genomic-based or transcriptomic-based biomarkers may hold the promise to establish predictive or prognostic stratification methods for ARDS, and also to help in developing novel therapeutic targets for ARDS. Notably, genetic/ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 115 publications
0
16
0
Order By: Relevance
“…Briefly, we searched MEDLINE, Embase, bioRxiv, medRxiv, the ARDS Database of Genes 55 , and the NCBI Gene Expression Omnibus from inception to April 1 st , 2023 without language restrictions. We also performed single-level backwards and forwards citation searches using SpiderCite 79 and hand-searched recent review articles 8083 .…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, we searched MEDLINE, Embase, bioRxiv, medRxiv, the ARDS Database of Genes 55 , and the NCBI Gene Expression Omnibus from inception to April 1 st , 2023 without language restrictions. We also performed single-level backwards and forwards citation searches using SpiderCite 79 and hand-searched recent review articles 8083 .…”
Section: Methodsmentioning
confidence: 99%
“…Improved comprehension of the risk factors of ARDS in patients with sepsis would enable clinicians to detect ARDS at an earlier stage. Additionally, various studies have altered the focus from clinical risk factors to biomarkers in order to predict the development of ARDS [ 25 , 26 ]. This is an approach towards more precise prediction and diagnosis for ARDS.…”
Section: Reviewmentioning
confidence: 99%
“…Much of the evidence regarding miRNA identification in ARDS comes from preclinical studies. MiRNAs are involved in several pathophysiologic processes, including regulation of cell proliferation, differentiation, apoptosis, metabolism, and the immune response [ 108 ]. Some transcriptomics analyses of miRNAs in preclinical models revealed that inflammation during ARDS promotes macrophage proliferation and inflammation, also of the lung [ 109 112 ].…”
Section: Omics In Ards Researchmentioning
confidence: 99%